COD REMOVAL PERFORMANCE USING MORINGA OLEIFERA SEEDS IN ABATTOIR WASTEWATER TREATMENT - Rahman, Arief; Arfi, Febrina; Harahap, Juliansyah; Shahira, Nadia (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2024)
High COD levels in abattoir wastewater might cause negative impact to the environment, hence it must be lowered before being discharged into the environment. The seeds of moringa plant (Moringa oleifera) contains quite high levels of protein compounds, makes it potential as biocoagulant in coagulation-flocculation process for wastewater treatment. The objective of this research is to discover the potential of biocoagulant from moringa seeds powder in decreasing COD levels on abattoir waste water treatment. The research was performed with biocoagulant dose variations 0 g; 0.5 g; 1 g; 1.5 g; 2 g; and 2.5 g, utilizing rapid mixing at 120 rpm, and slow mixing at 30 rpm with duration 2 and 30 minutes respectively. The result showing that the optimum dose obtained at 2 g, with percentage of decreation by 93.97%. Based on the research, it is concluded that the biocoagulant derived from moringa seeds can perform effectively in COD removal of abattoir wastewater treatment.